European Union subsidies and bank credits as external sources of financing for small and medium enterprises in Poland = Dotacje Unii Europejskiej oraz kredyty bankowe jako źródła finansowania zewnętrznego małych i średnich przedsiębiorstw w Polsce - Kata, Ryszard; Filip, Paulina (Zielona Góra: Faculty of Economics and Management Press)
The selection of financing sources constitutes an important decisive problem for small and medium enterprises. The study encompasses the assessment of which scale small and medium enterprises in Poland use EU funds and bank credits as the sources connected with financing business activity. Moreover, based on surveys of enterprises in Podkarpackie voivodship, the barriers and limitations of SMEs in the access to such financing sources have been defined. The classification and assessment of the significance of particular financial limitations have been performed by means of the reasons for credit passiveness of SMEs and their financial exclusion.
Keywords: MSP; małe i średnie przedsiębiorstwa; fundusze UE; finansowanie działalności; kredyty bankowe; SME sector; small and medium sized enterprises; EU funds; financing of activity; bank credit